2016
DOI: 10.1371/journal.pone.0149831
|View full text |Cite
|
Sign up to set email alerts
|

Does Subjective Rating Reflect Behavioural Coding? Personality in 2 Month-Old Dog Puppies: An Open-Field Test and Adjective-Based Questionnaire

Abstract: A number of studies have recently investigated personality traits in non-human species, with the dog gaining popularity as a subject species for research in this area. Recent research has shown the consistency of personality traits across both context and time for adult dogs, both when using questionnaire based methods of investigation and behavioural analyses of the dogs’ behaviour. However, only a few studies have assessed the correspondence between these two methods, with results varying considerably across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
(77 reference statements)
4
22
0
Order By: Relevance
“…Confirming previous results 15 and thereby adding robustness to our assessment tool, the cluster analysis extracted six main personality traits “Exuberant attitude”, “Cautious attitude”, “Relaxed attitude”, “Social interaction”, “Playful interaction” and “Non-stimuli related behaviour”.…”
Section: Discussionsupporting
confidence: 81%
“…Confirming previous results 15 and thereby adding robustness to our assessment tool, the cluster analysis extracted six main personality traits “Exuberant attitude”, “Cautious attitude”, “Relaxed attitude”, “Social interaction”, “Playful interaction” and “Non-stimuli related behaviour”.…”
Section: Discussionsupporting
confidence: 81%
“…In harmony with this, studies correlating video rating with questionnaire rating generally reported higher correlations (e.g. [ 60 , 87 ]) than those correlating video rating with video coding (e.g. [ 84 , 85 ]).…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, reactivity, protectiveness, and fearfulness are additional dimensions to the five-factor model. Reactivity emerged in several studies on non-human animals [ 3 , 5 , 7 , 32 , 35 ], while protectiveness has been previously used in the description of dogs’ personalities [ 8 ], but did not emerge in studies evaluating cats [ 7 , 9 ]. In cats, instead, some authors have identified dimensions such as dominant and curious [ 36 , 37 ] or human aggressive [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are different human perceptions and knowledge of dog and cat personalities. First, behavioural traits of dogs are widely recognised [ 9 , 17 , 35 ], while cats’ personalities, behavioural needs, sociality, and cat-human communication are still poorly understood [ 9 , 19 , 36 ]. Cats may use different communication tools from dogs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%